(untitled) (Research, Society and Development, 2020)
In Brazilian legal culture, Canon Law has always been assumed as a legitimate legal system and a contributor to the Brazilian legal system. This dialogical and collaborative approach is enshrined in constitutional law (art. 10, I CF/88) and in the Brazil-Holy See Agreement (Decr. 7107/2010). Indeed, its collaboration and articulation are the results of a political option of the Constituent Lawmaker of 1988. In this sense, the objective of this research is to analyze the cooperation of Canon law in the jurisprudence of Brazilian courts through empirical analysis. The jurimetrics approach produces a data collection of jurisprudence in the Courts of Justice of São Paulo, Minas Gerais and Ceará. From here emerges the question: how does Brazilian law apply Canon Law to litigation claims involving ecclesiastical entities? The methodology has a bibliographic and documentary source. As for the objective, it has an explanatory character and a quantitative and qualitative approach. The results achieved lead to the conclusion that the Canonical and Brazilian legal systems dialogue and collaborate for better application of the law in favor of ecclesiastical entities.